Distance education: the tutor under tutors’s perspective - Vilarinho, Lúcia Regina Goulart (2008)
The expansion of Distance Education has increased awareness about the tutor to whom roles of adviser / learning facilitator have been assigned: what he does, how became a tutor, what is required background to become a tutor and difficulties faced on his routine. To answer these questions, the research interviewed 26 tutors who participated in online group discussions about tutorship. Process encompassed forms applied containing closed and opened questions that provided qualitative and quantitative data. Numerical relations, percentages and contents analysis outlined the recurrences and contradictions in the answers received. The results indicated that: (a) most tutors did not receive specific training before exercising their tasks; (b) assumed their functions through a fortuitous process; (c) difficulties of their practice are pointed out to be consequence of the limitations of students and technology; (d) do not recognize the tutor as a teacher what is contradictory since attributions listed as specific of tutor are inherent to lecturing. The outlook of these subjects reflects the dual treatment received by the tutor in the pedagogical literature: sometimes seen as a stimulator, sometimes described as a teacher.